The Effect of Net Profit and Net Cash Flow on Market Capitalization (Case Study of Sharia Banking Companies at the Indonesia Stock Exchange 2019–2022 Period): Pengaruh Laba Bersih dan Arus Kas Bersih terhadap Kapitalisasi Pasar (Studi Kasus pada Perusahaan Perbankan Syariah di Bursa Efek Indonesia Periode 2019–2022) - Aulia Zahra, Ananda Putri; Rafsanjani, Haqiqi; Setiyowati, Arin (Perisai : Islamic Banking and Finance Journal, 2024)
Capital market players or investors will consider several elements that can indicate the state of the company, such as examining financial reports from cash flow to profit and loss statements. In addition, the company's share price will ultimately be related to its market capitalization value. The profits obtained by investors will increase along with the increase in stock market capitalization, and the greater the appreciation, the higher the level of profit from an alternative investment. This study aims to determine the effect of net income and net cash flow on market capitalization. Secondary data in the form of Sharia Banking quarterly financial reports that have been listed on the Indonesia Stock Exchange (IDX) for 2019-2022 is the source of the data. Three samples for this research sample were obtained, namely Bank Panin Dubai Syariah (PNBS), Sharia National Pension Savings Bank (BTPS), and Bank Syariah Indonesia (BSI). Panel data regression analysis with the Eviews 12 program was used in this study. The results show that partially net income has a negative and insignificant impact while net cash flow has a positive and significant impact on market capitalization. Meanwhile, market capitalization is simultaneously influenced by net profit and net cash flow variables.